How Is the Digital Age Shaping Young Minds? A Rapid Systematic Review of Executive Functions in Children and Adolescents with Exposure to ICT - Reinaldo Maeneja; Joana Rato; Inês Saraiva Ferreira (Children)
Objectives: This review assesses how daily exposure to Information and Communication Technologies (ICTs) affects executive functions in children and adolescents and explores the roles of parents in mitigating potential negative impacts on cognitive development and emotional regulation. Methods: Following PRISMA guidelines, a systematic search was conducted from 2022 to 2024 using PubMed, Scopus, and Cochrane Library. The study criteria included cohort studies, randomized controlled trials (RCTs), quasi-RCTs, and systematic reviews. Data extraction and risk-of-bias assessments were performed using ROBIS and ROBINS-E tools. Due to the heterogeneity of the results, a narrative synthesis was carried out. Results: Ten studies were included for analysis, comprising a total of 231,117 children from nine countries on three continents. Most studies indicated that excessive ICT exposure negatively affects executive functions, particularly working memory, inhibitory control, cognitive flexibility, and attention. Adverse effects were linked to increased screen time, poor sleep quality, and multitasking. However, two studies found no significant association, highlighting the influence of contextual factors like socioeconomic status, parental mediation, and screen content type. Shared ICT use with parents or siblings appeared to reduce negative effects. Conclusions: Excessive ICT exposure is associated with impaired executive function development in children and adolescents. Parental supervision and structured ICT use may mitigate risks. Future research should investigate moderating factors, such as socioeconomic status and ICT content, to develop guidelines for healthy digital engagement in youth.